Construction inventory and working capital an empirical analysis - Nur Nadia, Sallihah; Kumar, Senthil (UMP Press, 2021)
This research is an endeavour to understand the inventory problems faced by contructions companies in Pahang. The intention was to examine the level of inventory maintained by construction companies and its effect on their working capital. It was planned to analyse this information and suggest a suitable inventory model to manage the construction inventory more systematically. Purposive sampling technique was adopted to collect primary data on inventory and working capital from a few G7 contractors in Pahang. The data indicated that the companies were dealing with numerous types of inventories and that they were using labour intensive methods to manage the inventory. Apart from implementing FIFO and LIFO techniques, they were using ad hoc JIT approach to manage the inventory. Such random choice of techniques lead to simultaneous overages and outages among different category of inventories. Hence, it was recommended that the companies should implement ABC analysis to classify their inventory and implement computer based inventory management system, to overcome the overages and outages.